DELIBERATIVE LEADERSHIP AND POLITICAL LEGITIMACY: OPERATIONALIZING HABERMAS’S THEORY IN POST-REFORM INDONESIA - Noer, Hamka Hendra (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
Studies of deliberative democracy in Indonesia have yet to comprehensively investigate the influence of leadership on the quality of deliberation and its subsequent impact on political legitimacy. This gap creates a disjunction between normative ideals and the empirical realities of post-Reform political practices. This article analyzes the role of deliberative leadership in bolstering political legitimacy by operationalizing Jürgen Habermas's theoretical framework-communicative rationality, the public sphere, and communicative power-into empirically assessable indicators. Employing a rigorous qualitative methodology, this study undertakes a systematic review of academic publications, policy reports, and institutional documents published between 2015 and 2024. Data are analyzed using descriptive-analytical techniques informed by a deliberative systems perspective. The findings indicate that, notwithstanding the expansion of participatory mechanisms in the post-Reform era, deliberative practices in Indonesia remain largely procedural and symbolic. Institutional arenas such as Musrenbang, citizen forums, and digital public spaces exhibit deliberative potential but are constrained by oligarchic dominance, structural inequality, a weak legal culture, and institutional cooptation. The primary contribution of this article is the formulation of four operational indicators of deliberative leadership-participatory inclusiveness, quality of argumentation, transparency of policy reasoning, and institutional responsiveness-that advance deliberative democracy scholarship and provide an evaluative framework for strengthening political legitimacy and substantive democracy in Indonesia.